Enzymatic methods may underestimate the total serum bile acid concentration - Žížalová, Kateřina; Vecka, Marek; Vítek, Libor; Leníček, Martin (PloS one, 2020)
Enzymatic assays based on bacterial 3α-hydroxysteroid dehydrogenase are the method of choice for quantification of total bile acids (BAs) in serum. Although non-specific, it is generally considered precise and robust. The aim of this study was to investigate how changes in the BA spectrum might affect the reliability of the method. We measured standard solutions of twenty-three human and murine BAs using a commercial enzymatic assay and compared the measured vs. expected concentrations. Additionally, total BA concentrations in rat and human cholestatic samples with an abnormal BA spectrum were measured using an enzymatic assay, and a more specific LC-MS/MS method. We observed a great variability in the response of individual BAs in the enzymatic assay. Relative signal intensities ranged from 100% in glycocholic acid (reference) to only 20% in α-muricholic acid. The enzymatic assay markedly underestimated the BA concentrations in both human and rat cholestatic sera when compared to the LC-MS/MS assay. Our study indicated that the performance of an enzymatic assay largely depends on the BA spectrum, and the total concentration of BAs can be markedly underestimated. Samples with an atypical BA spectrum (viz. in rodents) should preferably be measured by other methods.
Keywords: Cholestasis; cholestáza; enzymatické testy; Reproducibility of Results; Rats; zvířata; 3-alpha-Hydroxysteroid Dehydrogenase (B-Specific); Humans; Bile Acids and Salts; Enzyme Assays; reprodukovatelnost výsledků; 3-alfa-hydroxysteroiddehydrogenasa (B-specifická); žlučové kyseliny a soli; krysa rodu Rattus; lidé; Animals